Residual stress within the porcelain veneer of 3-unit zirconia fixed dental prostheses with different framework designs measured by nanoindentation - Fardin, Vinicius Pavesi (2017)
The present study aimed to identify different concentrations of residual stress of surfaces of porcelain veneer (PV) fused to zirconia 3-unit fixed dental prostheses (FDPs) with even thickness and modified (lingual collar connected to proximal struts presenting 12 mm2 connector area) framework designs by nanoindentation method. Twenty-three FDPs replacing second premolar (PM) were fabricated and the cyclic loading was applied on twenty FDPs. Fractured, suspended and non-fatigued FDPs were selected and divided (n=3/each) into: 1) Fractured even thickness (ZrEvenF); 2) Suspended even thickness (ZrEvenS); 3) Fractured with modified framework (ZrModF); 4) Suspended with modified framework (ZrModS); 5) Non-fatigued even thickness (Control). Moreover, the control group surfaces could be divided (n=3/each) into: 6) Mesial PM abutment (MPMa); 7) Distal PM abutment (DPMa); 8) Buccal PM abutment (BPMa); 9) Lingual PM abutment (LPMa); 10) Mesial PM pontic (MPMp); 11) Distal PM pontic (DPMp); 12) Buccal PM pontic (BPMp); 13) Lingual PM pontic (LPMp); 14) Mesial molar abutment (MMa); 15) Distal molar abutment (DMa); 16) Buccal molar abutment (BMa); 17) Lingual molar abutment (LMa). The PV surfaces were nanoindented in regions of interest (ROI) 1, 2 and 3, which were 0.03 mm, 0.35 mm and 1.05 mm from outer PV surface surface towards the PV/framework interface, respectively. Each ROI received 5 nanoindentations with 10 m of minimum separation loaded to a peak load 4 N. The Linear Mixed Model test and Least Significant Difference (95%) were used. The statistical analysis among ZrEvenF, ZrEvenS, ZrModF, ZrModS, and Control groups showed differences (p=0.000) except for the comparison between ZrModS and Control group (p=0.371). Also, ROI 1, 2, and 3 were different (p<0.001) with higher residual stresses in outer PV regions relative to those closer to the framework. The comparison among crowns showed that pontic was different from premolar (p=0,001) and molar (p=0,007) abutments, always showing higher residual stress levels. When marginal ridges groups (MPMa, DPMa, MPMp, DPMp, MMa, DMa) were compared, the DMa group was different from DPMp (p=0,004) and MPMa (p=0,00) group, whereas MPMa was different among all groups. The residual stress of porcelain veneer FDPs was different between: fractured and suspended FDPs regardless of the framework design; ROI 1, 2 and 3; and pontic and abutment crowns. Moreover, the proximal areas presented the highest concentration of residual stress.